ANALISIS KESIAPAN DAN PERSPEKTIF GURU TERHADAP IMPLEMENTASI PEMBELAJARAN STEM DI SD MUHAMMADIYAH GENDENG - Saputra, Ricki Fahma Adi; Sabriyandi, Sabriyandi; Melani Dessy Tri Kusumawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze teachers’ readiness and perspectives regarding the implementation of STEM education at SD Muhammadiyah Gendeng. Qualitative methods (in-depth interviews, participatory observation, and documentation) were used to collect data. The results indicate that teachers’ readiness is in the “adequate” category; their main strengths are positive attitudes and the use of basic technology, while pedagogical, professional, and infrastructure aspects still require further strengthening. Teachers recognize the benefits of STEM in enhancing students’ critical thinking skills and creativity; however, barriers to interdisciplinary integration and limited facilities hinder implementation. The findings highlight the gap between teachers’ positive perceptions and their readiness for implementation, underscoring the importance of integrated policy support. The novelty of this research lies in its comprehensive analysis that simultaneously links teachers’ readiness and perspectives, particularly in religious-based elementary schools. Policy implications include enhancing continuous professional development programs for teachers, providing adequate technological facilities, and developing more operational STEM implementation guidelines to support STEM implementation in elementary schools. This study enriches the elementary-level STEM literature with holistic contextual insights and is expected to drive the strengthening of relevant policies.